2022
DOI: 10.31234/osf.io/j2bzc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional MRI correlates of inflammation in bipolar disorder: a systematic review

Abstract: Bipolar disorder (BD) is a common affective disorder characterized by recurrent oscillations between mood states and associated with inflammatory diseases and chronic inflammation. However, data on MRI abnormalities in BD and their relationship with inflammation are heterogeneous and no review has recapitulated them. In this pre-registered (PROSPERO: CRD42022308461) systematic review we searched Web of Science Core Collection and PubMed for articles correlating functional or structural MRI measures with immune… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Overall, the causal relationships between depression and cardiovascular risk (of stroke in particular) that have been identified (Cai et al, 2019;Gill et al, 2019;Lu et al, 2021) are particularly interesting considering the increasing evidence on depression and serotoninergic axis dysregulation as important players in stroke physiopathology (Colpo et al, 2019;Damsbo et al, 2019;Saccaro et al, 2022a). While the present review did not identify a definitive causal link between systemic inflammation and psychiatric disorders (the results on SCZ, MDD, or BD patients, for example, are not conclusive), the link between inflammation and psychiatric disorders is another topic of major interest in recent years (Wium-Andersen et al, 2016;Han and Ham, 2021;Murphy et al, 2021;Saccaro et al, 2021aSaccaro et al, , 2021bSaccaro et al, 2022b), and further studies, employing MR as well, could unravel the pathophysiological role of inflammation in psychiatric disorders, with diagnostic, prognostic or therapeutic potential. To do so, however, it is important to focus on the right targets and to correctly interpret results.…”
Section: Discussion and Limitationsmentioning
confidence: 68%
See 3 more Smart Citations
“…Overall, the causal relationships between depression and cardiovascular risk (of stroke in particular) that have been identified (Cai et al, 2019;Gill et al, 2019;Lu et al, 2021) are particularly interesting considering the increasing evidence on depression and serotoninergic axis dysregulation as important players in stroke physiopathology (Colpo et al, 2019;Damsbo et al, 2019;Saccaro et al, 2022a). While the present review did not identify a definitive causal link between systemic inflammation and psychiatric disorders (the results on SCZ, MDD, or BD patients, for example, are not conclusive), the link between inflammation and psychiatric disorders is another topic of major interest in recent years (Wium-Andersen et al, 2016;Han and Ham, 2021;Murphy et al, 2021;Saccaro et al, 2021aSaccaro et al, , 2021bSaccaro et al, 2022b), and further studies, employing MR as well, could unravel the pathophysiological role of inflammation in psychiatric disorders, with diagnostic, prognostic or therapeutic potential. To do so, however, it is important to focus on the right targets and to correctly interpret results.…”
Section: Discussion and Limitationsmentioning
confidence: 68%
“…Interestingly, two articles focused on causal risk factors for early-onset MDD (Michalek et al , 2017; Sequeira et al , 2017). The latter (Sequeira et al , 2017) showed that genetic liability to early menarche was causally associated with higher levels of depressive symptoms at 14 years but not after 14 years. The first one (Michalek et al , 2017) found that genetic predisposition to shorter telomere lengths was causally associated with increased risk for childhood-onset MDD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations